HCV/HIV coinfection among people who inject drugs and enter opioid substitution treatment in Greece: prevalence and correlates. Issue 1 (December 2016) - Fotiou, Anastasios; Kanavou, Eleftheria; Antaraki, Argyro; Richardson, Clive; Terzidou, Manina; Kokkevi, Anna
Abstract Background HCV/HIV coinfection in people who inject drugs is a public health issue, which presents a variety of challenges to healthcare providers. The determinants of HCV/HIV coinfection in this population are nonetheless not well known. The aim of the present study is to identify the factors associated with HCV/HIV coinfection in people who inject drugs and enter drug-related treatment. Methods Linked serological and behavioral data were collected from people who entered 38 opioid substitution treatment clinics in central and southern Greece between January and December 2013. Three mutually exclusive groups were defined based on the presence of HCV and HIV antibodies. Group 1 clients had neither infection, Group 2 had HCV but not HIV, and Group 3 had HCV/HIV coinfection. Multinomial logistic regression analyses identified differences between groups according to socio-demographic, drug use and higher-risk behavioral characteristics. Results Our study population consisted of 580 people who injected drugs in the past 12 months (79.8 % males, with median age 36 years).79.4 % were HCV and 15.7 % HIV infected. Of those with complete serological data in both HCV and HIV indicators, 20.4 % were uninfected, 64.0 % HCV monoinfected, and 14.9 % HCV/HIV coinfected. HCV infection with or without HIV coinfection was positively associated with living alone or with a spouse/partner without children, prior incarceration, drug injecting histories of ≥10 years, and syringe sharing in the past 12 months, and negatively associated with never having previously been tested for HCV. HCV/HIV coinfection, but not HCV infection alone, was positively associated with residence in urban areas (relative risk ratio [RRR] = 4.8, 95 % confidence interval [CI]: 1.7–13.7, p  = 0.004) and averaging >3 injections a day in the past 30 days (RRR = 4.5, 95 % CI: 1.6–12.8, p  = 0.005), and negatively associated with using a condom in the last sexual intercourse. Conclusions People who inject drugs and live in urban areas and inject frequently have higher risk of coinfection. Findings highlight the need for scaling-up needle and syringe programs in inner city areas and promoting access of this population to screening and treatment, especially in prisons. The protective role of living with parents and children could inform the implementation of indicated interventions.